Illness Perception and Quality of Life of Parents with Thalassemic Adolescents - Lestari, Andini Tri; Mardhiyah, Ai; Pahria, Tuti; Mediani, Henny Suzana; Hendrawati, Hendrawati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Thalassemia major necessitates routine treatment that affects the physical, psychological, and social capacities of both the sufferers and their parents. In these circumstances, the way parents perceive their child's illness significantly influences their quality of life, making this a crucial aspect to consider.Objective: This study aims to explore the relationship between illness perception and quality of life in parents of adolescents with thalassemia major at RSUD dr. Slamet Garut. Method: The study employed a cross-sectional approach, including 64 parents of adolescents with thalassemia major (aged 10-18 years) selected through consecutive sampling. The Brief Illness Perception Questionnaire (BIPQ) was used to measure illness perception, and the World Health Organization Quality of Life Brief Version (WHOQoL-BREF) was used to assess quality of life. Both instruments are validated and reliable, with BIPQ having reliability coefficients of r=0.40-0.78 (α=0.74) and WHOQoL-BREF having r=0.39-0.79 (α=0.94). The Spearman correlation test was utilized for bivariate analysis. Results: The findings indicated that 55 respondents (85.9%) had a positive illness perception of thalassemia, and 61 respondents (95.3%) reported a high quality of life. The correlation analysis revealed a significant relationship between illness perception and the quality of life of parents, with a correlation coefficient of 0.548 (p<0.05). Conclusions: This concludes that there is a significant relationship between illness perception and quality of life in parents of adolescents with thalassemia major at RSUD dr. Slamet Garut.